2018
DOI: 10.2478/jdis-2018-0004
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Visualizing Research Collaboration and Productivity

Abstract: Purpose This paper presents findings of a quasi-experimental assessment to gauge the research productivity and degree of interdisciplinarity of research center outputs. Of special interest, we share an enriched visualization of research co-authoring patterns. Design/methodology/approach We compile publications by 45 researchers in each of 1) the iUTAH project, which we consider here to be analogous to a “research center,” 2) CG1— a comparison group of participants in two other Utah environmental research cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In general, research productivity of female professors has been found to be lower when compared to their male counterparts (Cui, Ding, & Zhu, 2022; Garner, Porter, Leidolf, & Baker, 2018; Sá, Cowley, Martinez, Kachynska, & Sabzalieva, 2020). This is the case with OA publishing as well, confirming existing studies which found that male professors are more likely to author OA articles because female faculty are usually less funded (Nguyen, Nguyen, Le, Ho, & Vuong, 2021; Olejniczak & Wilson, 2020; Zhu, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In general, research productivity of female professors has been found to be lower when compared to their male counterparts (Cui, Ding, & Zhu, 2022; Garner, Porter, Leidolf, & Baker, 2018; Sá, Cowley, Martinez, Kachynska, & Sabzalieva, 2020). This is the case with OA publishing as well, confirming existing studies which found that male professors are more likely to author OA articles because female faculty are usually less funded (Nguyen, Nguyen, Le, Ho, & Vuong, 2021; Olejniczak & Wilson, 2020; Zhu, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Researchers that adopt Open Innovation schemes and collaborations have increased the number of published research articles and produced patents [47]. Moreover, it has also been observed that besides an increased publication rate, citations at these articles are also higher compared to the citations accrued before the collaboration.…”
Section: Advantages In Researchmentioning
confidence: 99%
“…Despite the rather large number of definitions and interpretations of interdisciplinarity, specific measurement tools of interdisciplinary orientation-a paramount dimension within the research interdisciplinarity framework (Stokols, 2013)-are rather scarce. There are very few scales available and they either focus on fragmentary facets of interdisciplinarity (such as research collaboration and productivity) or on specific disciplines, like engineering or medicine (Garner et al, 2018;Kirby et al, 2019;Lattuca et al, 2012;Misra et al, 2015;Stokols et al, 2005). As Kirby et al (2019: 2) noticed, 'the largest disciplinary divide among scientists is that between the natural sciences (examining biological, physical, and chemical processes) and the social sciences (examining human dimensions of the world).…”
Section: Theoretical Model Developmentmentioning
confidence: 99%